Pola Deformasi Shear Connector Berdasarkan Pengaruh Variasi Panjang Dengan Permodelan Menggunakan Perangkat Lunak ANSYS 15.0 - Rahma Nindya Ayu Hapsari; Adhe Verdianto Hidayat; Edrial Sulistiyo (Jurnal Teknik Sipil Unaya, 2022)
Composite structure is a structure that consists of several materials with different material properties and forms a single unit with the aim of producing better composite properties. In order for the steel-concrete composite structure to work properly, a shear connector is needed that unites the steel beam and the concrete slab so that it does not shift. This study uses ANSYS 15.0. The simulation used is the Static Structural method with non-linear materials for both steel and concrete. The length variation observed for comparison is the length of the stud connector from 10 mm to 100 mm with a fixed stud diameter of 10 mm. The tendency of the deformation pattern that occurs in the stud connector is the occurrence of deformation in the form of vertical bending at the stud connection with the weld. The results of numerical analysis show that the addition of the diameter of the shear connector of the stud type affects the load capacity that the stud can withstand. The larger the diameter of the stud, the greater the load that can be carried. This is because along with the increase in the diameter of the stud, it causes the surface area to be loaded to increase, so that occurs the greater stress.